Diel mercury concentration variations in a mercury-impacted stream. Issue 8 (13th July 2022) - Brooks, Scott C.; Riscassi, Ami L.; Miller, Carrie L.; Lowe, Kenneth A.; Yin, Xiangping; Mehlhorn, Tonia L.
Abstract : Diel patterns in mercury and methylmercury concentration were studied at several distinct locations (downstream forested, midstream urban/suburban, upstream industrial) along a mercury-contaminated creek in summer and winter. Abstract : Filtered and particulate mercury (Hg) and methylmercury (MMHg), and associated water chemistry parameters, were evaluated bi-hourly for several 30 h periods during the summer and winter seasons at several distinct locations (downstream forested, midstream urban/suburban, upstream industrial) along a creek contaminated with high levels of inorganic Hg to determine if biogeochemical Hg and MMHg cycles respond to the daily photocycle. In summer particulate Hg and MMHg concentrations doubled overnight (excluding the upstream industrial site) concurrent with increases in turbidity and total suspended sediment; no such pattern was evident in winter. Seasonal and diel changes in the activity of macrobiota affecting the suspension of contaminated sediments are likely responsible for these patterns as other potential explanatory variables ( e.g., instrument drift, pH, discharge) could not account for the range and timing of our observations. Diel patterns in filtered Hg (HgD ) were significant only at locations and times of the year when channel shading was not present and daytime concentrations increased 22–89% above nighttime minima likely caused by direct and indirect photochemical reactions. Relationships between HgD and dissolved organic carbon (DOC) concentration or character were inconsistent between sites. Unlike HgD, there were significant diel patterns in filtered MMHg (MMHgD ) at all sites and times of year, with summer concentrations peaking in mid to late afternoon while the timing differed in winter, with concentrations peaking after sunset. Daily variability in MMHgD concentration ranged between 25 and 75%. The results imply key controls on net methylation occur within the stream or on the stream bed and include factors such as small-scale temperature changes in the water column and photosynthetic activity of stream biofilm. With respect to stream monitoring, results from this study indicate (1) consistent timing in stream Hg and MMHg sampling is required for accurate assessment of long-term trends, (2) in situ measurements of turbidity can be used to quantify diel dynamics of both particulate Hg and MMHg concentrations, and (3) in situ fluorescing dissolved organic matter (FDOM), a potential proxy for DOC, was not capable of resolving diel dynamics of filtered Hg or MMHg.